PENGEMBANGAN PETERNAKAN AYAM BROILER SEBAGAI ALTERNATIF PENINGKATAN EKONOMI DAN KETAHANAN PANGAN MASYARAKAT DI NAGARI SAKO PASIA TALANG KABUPATEN SOLOK SELATAN - Sosmiarti Sosmiarti; Yuliati Shafan Nur; Arfai Arfai; Andani Eka Putra (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
In Nagari Sako Pasia Talang, Sungai Pagu District, South Solok Regency, the scarcity of accessible animal protein sources coupled with limited employment opportunities poses a considerable socio-economic challenge. This programme was designed to enhance household incomes and fortify food security through the structured development of broiler poultry farming. The implementation strategy encompassed community outreach via structured training sessions and hands-on workshops, alongside expert consultations facilitated by academics from Andalas University. An integrated educational and participatory approach was employed, incorporating technical training in broiler husbandry, the construction of standardized poultry housing, feed formulation utilizing locally available ingredients, livestock health management, and farm business financial analysis. Tangible support was also provided in the form of poultry housing units, day-old chicks (DOC), feed supplies, and essential farming equipment. The intervention yielded marked improvements in both the knowledge base and practical skills of participating community members, enabling the adoption of efficient, locally adaptive broiler farming techniques. A pilot, collectively managed poultry enterprise was successfully established, producing 970 market-ready broilers from an initial stock of 1,020 DOC, while achieving a competitive feed conversion ratio (FCR). Financial analysis revealed a potential net profit of IDR 9,131,160 per 35-day production cycle, underscoring the venture’s economic viability. Beyond income generation, the programme broadened community access to affordable and nutritious animal protein, and catalyzed the emergence of new, livestock-based entrepreneurial models. With its demonstrable success, the initiative holds significant potential for replication as a sustainable, village-centered strategy for economic resilience and food security.